Role of Fintech for Credit Analysis of MSMEs - Geetha Rajaram; Vidya CM (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2022)
Financial technology or fintech is used extensively in evaluation of the creditworthiness of a business or organization. The primary problem faced by small and medium enterprises is obtaining loan for starting or improving their business, due to lack of hard information and good repute. Sources for hard information are historic data like audited balance sheets, forecasts in theform of budgets and cash flow, ratings given by credit rating companies, analysis of ratios, capital marketization, share prices and many more benchmarks. Micro, small and medium enterprises (MSMEs) face the problem of information asymmetry. In other words, it is the analysis of the ability of a company to honor its financial obligations. The in thing in today’s world is “big data”.The credit rating companies have experienced a sea change. Numerus data is collected every second from various sources, social media sites, online purchases, off-line purchases. The emerging era of credit analysis is based on consumer behavior, the likes and dislikes one expresses on social media sites to the analysis on one’s preference for the products they purchase,to the emotions one expresses, everything is recorded through data “Big Data”. Each and everything are accessible within minutes, to know whether a person is worthy of credit or not. All these are studied through complicated mathematical computations to analyze sequences of information within an ocean of data. These credit scorings can be provided within no time and are equally cost efficient, but it is also intruding to one’s privacy. The study is on how effective is Big Data for credit analysis.